Early detection of myocarditis caused by immune checkpoint inhibitor therapy with nivolumab and ipilimumab for advanced recurrent renal cell carcinoma - Maki Todo; Yodo Gatate; Shintaro Nakano; Go Kaneko; Masayuki Hagiwara; Takayuki Takahashi; Yuta Umezawa; Genji Ueda; Shiho Ishikawa; Yoshinori Makino; Masafumi Oyama; Suguru Shirotake (Cancer Immunology, Immunotherapy)
Abstract Combination therapy with nivolumab and ipilimumab for advanced renal cell carcinoma (RCC) may cause immune-related myocarditis; however, its incidence in this cancer type and regimen remains unknown. At our institution, we measure biomarkers, such as high-sensitivity Troponin (hsTn), and perform electrocardiograms (ECGs) and echocardiography before and every month after the initiation of this therapy, and the findings obtained and patients’ symptoms are continuously monitored by physicians and pharmacists. A retrospective survey was conducted on physiological and biochemical test findings and immune-related adverse events in patients with advanced RCC who received combination therapy with nivolumab and ipilimumab between October 1, 2018 and December 31, 2023. Patients suspected of having myocarditis consulted with cardiologists. Myocarditis due to this therapy was detected in 5 of the 86 patients (5.8%) assessed using the European Society of Cardiology 2022 guidelines. There were no fatal symptoms or death due to myocarditis. The median time to the onset of myocarditis was 25 days (21–86 days). The early detection of myocarditis caused by this therapy requires the monitoring of changes by periodically measuring hsTn and other cardiac markers and performing ECGs and echocardiography from the early stages of administration through to the end of treatment. In addition to checking symptoms, if these abnormalities are detected and myocarditis is suspected, prompt collaboration with cardiologists is recommended. Our management strategy of care by a onco-cardiology team may contribute to the early diagnosis and treatment of myocarditis.